Pengaruh Kombinasi Hidroksipropil Metilselulosa-Xanthan Gum sebagai Matriks Pada Profil Pelepasan Tablet Teofilin Lepas Terkendali - Iskandarsyah, Iskandarsyah; Sutriyo, Sutriyo; Hayati, Dian (Majalah Ilmu Kefarmasian, 2010)
Theophylline is a bronchodilator used for the treatment of bronchial asthma and other respiratory diseases. Theophylline has a narrow therapeutic index (10-20 µg/ml) and relatively short elimination half-life (6,19 ± 0,031 hours). Causes rapid elimination rate of theophylline should be given periodically to maintain drug levels in blood for the desired therapeutic effect can be achieved. The preparation of theophylline controlled release is expected to produce blood concentrations of theophylline in a more stable. The physical properties of tablets and drug release from matrix systems are influenced by the nature of the composition of the matrix. This research, theophylline controlled release tablets were made by combination of xanthan gum and HPMC as matrix composition. Combination of HPMC and xanthan gum was supposed to produce tablets with the required pysical properties and ability to extend the releasing period of theophylline from matrix system. HPMC-xanthan gum compositions used in formulation were 1:4, 1:1, and 4:1. Based on the evaluation of the physical properties carried out on the tablet, it was found out that the three formulas fit the requirements for ideal tablet. The increasing of xanthan gum concentration in the formula was proportional with the improvement of mass flowability and tablet hardness. Evaluation of the releasing profile of theophylline from matrix system had been conducted in vitro by dissolution test. Based on the test, it was found out that all combinations have variation in releasing profile. The increasing of HPMC concentration in formula will extend the releasing time of theophylline. The difference in releasing profile of Retaphyl SR® with formula 1, 2, and 3 because of differences in raw materials that form the matrix.